Scientific and Methodical Principles of Formation of Informational and Analytical Support for Assessing the Influence of Social Determinants on the Economic Security of the National Economy. (Economics and region, 2018)
On the basis of generalization and systematization of the methodology of international rating assessment of the development of national economies and their various aspects, an approach is proposed to identify social determinants that affect the economic security of the national economy and comprehensively represent the state and dynamics of processes in society: the demographic state; health of the nation and medical care; welfare and living conditions; innovative development and education of the population; harmony in the society. The stages of formation of informational and analytical support for assessing the influence of social determinants on economic security of Ukraine are proposed. The selection of indicators describing the system-forming influence of social determinants on the development of the national economy and the state of its economic security is carried out. The comprehensive assessment of system-forming groups of social determinants of economic security is distinguished.
Keywords: information and analytical support; social determinants; economic security; national economy; risks and threats.